The economic and social impact of privatisation of state-owned enterprises in Africa - .Obadan, Michael I. (Green book series / CODESRIA, 2008)
The case for privatization, whether defined in a broad or narrow sense, has been forcefully made by its advocates against the backdrop of the much advertised poor performances of state-owned enterprises (SOEs) and theoretical arguments relating to the efficiency of private firms over public enterprises. [...] In spite of this, since the late 1980s, privatization has been stepped up in almost all African countries. And after about two decades of vigorous implementation of privatization programmes in Africa, there is a compelling need for a comprehensive and systematic analysis of various privatization issues, particularly the economic and social impact. This book thus establishes a clear case for a comprehensive and systematic analysis of the impact of privatization in Africa. Specifically, the book provides a state-of-the art review of privatization issues and research questions as a prelude to an in-depth study of the economic and social impact of privatization. In the light of the rich insights brought to bear on the issues, this book should stimulate the interest of researchers, donors and policy makers to undertake or support the follow-up in-depth research envisaged.